KOMBINASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW II DAN NUMBERED HEAD TOGETHER PADA HASIL BELAJAR MATEMATIKA SISWA SMA NEGERI 3 SORONG - Faisal Eka Mahendra (Qalam : Jurnal Ilmu Kependidikan, 2016)
This research aim to see the differences between conventional learning and cooperative learning types jigsaw II and NHT combination. In this research, sampling technique using is simple random sampling in tenth science five as an experiment class (method implemented) and tenth science four as an control class (conventional class). The datas about experiment, control class, and experiment try out collecting from documentation method. The test will be given after implementation has done in experiment class and will be given the same test in control class without the implementation. Each RPP signification in t-test are: first RPP is 0,42 < 0,05, second RPP is 0,003 < 0,05, the third is 0,000 < 0,05. The difference will be seen ini t_count > t_table, they are 2,083 > 2,004; 3,084 > 2,004; and 6,982 > 2,004. This shows that t_count > t_table, so Ha being accepted. That means, the average of student's outcomes of experiment class which teachs by jigsaw II and NHT combination really has the difference from conttol class. In this research the average of experiment class is 66,24 when control class is 43,73. It clearly shows that the average of experiment class higher than control class.